The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1071/cp19115
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of axillary buds of sugarcane at different cutting stages: evidence for alterations in axillary bud gene expression

Abstract: Productivity of sugarcane (Saccharum spp.) crops varies at each cutting stage, reaching critical rates close to the fifth cut (fourth ratoon). Knowledge of proteins involved in the regrowth of sugarcane within the cutting process is important for the development of cultivars with greater longevity. The present study presents new information that the proteome of axillary buds is changed in successive cuts in sugarcane culture. Proteins were identified by UPLC-ESI-Q-TOF (ultra-high-performance liquid chromatogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Quantification by spectral counting is a labelfree quantification method, which is efficient and low cost (Liu et al 2004;Old et al 2005). Proteomic studies have been used to study developmental changes in sugarcane (Maranho et al 2019), and salt stress was shown to induce changes in the proteomic profile of micro-propagated sugarcane shoots (Passamani et al 2017). However, there are no published proteomic studies on sugarcane plants growing in saline soil.…”
Section: Introductionmentioning
confidence: 99%
“…Quantification by spectral counting is a labelfree quantification method, which is efficient and low cost (Liu et al 2004;Old et al 2005). Proteomic studies have been used to study developmental changes in sugarcane (Maranho et al 2019), and salt stress was shown to induce changes in the proteomic profile of micro-propagated sugarcane shoots (Passamani et al 2017). However, there are no published proteomic studies on sugarcane plants growing in saline soil.…”
Section: Introductionmentioning
confidence: 99%